Terrorism as Economic Warfare: America's Risky Business - Rodger A. Bates; Bryan LaBrecque (Journal of Public and Professional Sociology, 2019)
Terrorism is a form of asymmetrical warfare. Terrorists employ a variety of tactics to threaten and intimidate a group or society. Technology is an important force multiplier which may allow them engage in cost-effective actions frequently directed at economic targets. As a means of economic warfare, terrorism can disrupt, demoralize and severely diminish the ability of a group to counter the threat of a terrorist group. It is America's risky business.